HYBRID RESOURCE PROVISIONING SYSTEM FOR VIRTUAL NETWORK FUNCTIONS - Sulima, S.V.; Skulysh, M.A. (Radio Electronics, Computer Science, Control, 2017)
Context. The problem of growth of the mobile data traffic and the number of services becomes global, moreover, volume and frequency of control traffic transmitted through the network are increasing, and therefore there is a need for its effective management to ensure the quality of service required by users and optimal use of mobile network resources. In such circumstances, the load on the server that is created in the process of establishing the connection and its serving has its considerations. Dynamic resource provisioning is a useful technique for handling the variations seen in communication systems workloads. Virtualization technology allows to implement this approach. An analytic model of a system would be attractive as it would be able to evaluate system characteristics under a wide range of conditions, and to be computed comparatively easily. It is also can incorporate numerical optimization techniques for system design. Objective. To improve the efficiency of mobile network through optimal resource allocation in telecommunication environment. Method. Analysis of the known publications devoted to virtualization of network functions of mobile network has shown the modeling approach to resource allocation and also has shown the absence of decisions on important issues of this process (performance of management, load prediction system). Results. An approach to model and investigate hybrid dynamic system of network functions resource management, where resources are provided to virtual nodes dynamically and opportunistically based on predicted needs, is proposed. Conclusions. In the paper the problem of provisioning system design for virtualized network functions is solved. A method for adapting the size of network function’s resource allocation control interval is proposed that provides dynamic configuration of the system, reducing excessive service data transmitted in the network, and decrease the load of network nodes. The workload service system model is built which outlines a method of workload forecasting, which takes into account long-term accumulated statistics and recent trends observed in a network that allows a rational level of management costs and final values of quality of service.